PERTANGGUNGJAWABAN PIDANA PELAKU PROSTITUSI ONLINE MENGGUNAKAN SARANA APLIKASI MICHAT - Jagad, Rony Piwulang; Hartoyo (Lex Journal: Kajian Hukum & Keadilan, 2022)
The main problem of the research is how is the criminal liability of online prostitutes using the application. In the main issue, the problem will be formulated in several sub-problems, namely: 1) How is the legal regulation of online prostitution using the Michat application?, 2) How are the criminal acts of online prostitution using the Michat application? ?, 3) how is the criminal liability for online prostitution actors using the michat application?. This research uses normative legal research methods and this research is descriptive. The results of the study show that: 1) The legal basis for ensnaring perpetrators of online prostitution are articles 282 and 289 of the Criminal Code, article 27 paragraph (1) in conjunction with article 45 paragraph (1) of Law number 11 of 2008 concerning ITE and articles 29, 30 of the Law - Law number 44 of 2008 concerning Pornography. 2) The elements of online prostitution are subjective elements, objective elements and unlawful acts. 3) Criminal liability in the form of imprisonment, fines and social sanctions. Keyword :Criminal Liability, Online Prostitution, Michat